Board of directors and top management team. CEO relative power and financial returns in Brazil - Schalka, Beatriz (2014)
This article investigates if companies with a stricter control and monitoring system perform better than others in Brazil. The works compares 116 companies in respect to the their independence level between top management team and board directors– being that measured by four parameters, namely, the percentage of independent outsiders in the board, the separation of CEO and chairman, the adoption of contingent compensation and the percentage of institutional investors in the ownership structure – and their financial return measured in terms return on assets (ROA) from the latest Quarterly Earnings release of 2012. Two variables (percentage of outside directors and percentage of institutional investor ownership) are significant in the regression. This paper has provided evidences that the increase in the formal governance structure trough outside directors in the board and ownership by institutional investor might actually lead to worse performance.